Hierarchical Micro-nano Surface Roughness Wax-impregnated Cotton Fabrics Platform For Cell-based Diagnostics - Norsamsiah M. Wahab; Asnida A. Wahab; Fadzilah A. Abdul Majid; Mohammed R. Abdul Kadir; Hadi Nur; Muhammad Qadri Effendy Mubarak (ACS Publication, 2025)
Indexed by WOS/Scopus/ERA (Tier 2)